FROM THE MAGISTRAL FORMULA TO THE INDUSTRIAL MEDICINE IN MEXICO: THE CASE OF THE SPECIFIC ZENDEJAS, 1891-1937 (Tzintzun, Revista de Estudios Históricos, 2023)
The objective of this article is to analyze the case of the medicine in Mexico atthe beginning of the 20th century known as Zendejas Specific, its maincharacteristics, as well as the legal disputes and controversies that took placeregarding its distribution and commercialization. The study shows thetransformation of the Mexican pharmacy that occurred during these decades,characterized by the adoption of industrial medicine and the abandonment ofthe use of medicinal plants, as well as by the implementation of pharmaceuticallegislation based on modern scientific principles.
Keywords: history of pharmacy; Mexico; Specific Zendejas; industrial medication; master formula; pharmaceutical industry